Pengaruh Latihan Drop Pass dan Pass Team Competition Terhadap Passing Stopping Dalam Permainan Sepakbola - Azizul Umam; Soemardiawan Soemardiawan; Ismail Marzuki; Nurdin Nurdin; Fitri Anggraini (Universitas Hamzanwadi, 2026)
The players of Kerame Jati FC have poor dribbling skills, as evidenced by frequent turnovers, poor balance, and sluggish movement when facing opponents. This study aims to determine the effects of 1-on-1 after dribbling drills and dribbling drills with a curving line trajectory. The experimental method, using a two-group pretest-posttest design, involved 22 players divided into two groups (n=11). Group A received 1-on-1 after dribbling training, while Group B received dribbling training with a curving line trajectory. The test instrument was a dribbling test. Data analysis used the paired-sample t-test and the independent-samples t-test. The results showed that 1-on-1 after-dribbling training had a significant effect (calculated t = 8.247 > table t = 2.228, p = 0.000), with an average time reduction from 18.45 seconds to 14.82 seconds. Dribbling practice with a curving line trajectory also had a significant effect (calculated t = 6.924 > critical t = 2.228, p = 0.000), resulting in a decrease in average time from 18.52 seconds to 15.45 seconds. There was a significant difference in effect between the two drills (t-calculated 2.154 > t-table 2.086, p = 0.044), with the 1-on-1 after dribbling drill proving superior. In conclusion, both drills are effective at improving dribbling skills; however, the 1-on-1 after dribbling drill is superior and is recommended for training programs.